Creative teaching in science and health effect on pupil creativity and achievement - Vicencio, Evelina Maclang
This study investigated the effects of a divergent-convergent teaching model on the creativity and achievement in science and health of grade 4 pupils, as measured by their performance in their creativity test and a teacher-made schievement test in science and health. Results show that creative teaching enhances pupils' creativity in the dimensions of originality, abstractness, and elaboration and their achievement in science and health. In matters of creativity, however, it fails to significantly enhance fluency and resistance to premature closure. Since no difference occurs between male and female respondents, gender has no effect on creativity.
Originally presented as the author's thesis; University of the Philippines, 1991.
Keywords: Creative ability in children; Teaching -- Philippines -- Manila Metropolitan Area -- Aids and devices; Science -- Sudy and teaching (Elementary) -- Philippines -- Manila Metropolitan Area; Health education -- Philippines -- Manila Metropolitan Area; Fourth grade (Education) -- Philippines -- Manila Metropolitan Area; Academic achievement -- Philippines -- Manila Metropolitan Area